Peningkatan Hasil Belajar Perkalian Pecahan dan Desimal Menggunakan Model Problem Based Learning di Kelas V SDN 34 Pasar Baru Kabupaten Pesisir Selatan - Elsa Hasnatul Alia; Masniladevi Masniladevi (Universitas Negeri Padang, 2025)
This research was motivated by the low learning outcomes for the multiplication of fractions and decimals in Class V of SDN 34 Pasar Baru, Pesisir Selatan Regency. This research aims to describe how to improve learning outcomes in the multiplication of fractions and decimals using the Problem-Based Learning (PBL) model in Class V of SDN 34 Pasar Baru, Pesisir Selatan Regency. This research is classroom action research that uses two types of approaches: qualitative and quantitative. The subjects in this research were 20 class V teachers and students. The research was carried out in two cycles, in each cycle there were four stages, namely planning, implementation, observation and reflection. Data collection techniques use observation sheets, tests and non-tests. The results of the research showed that there was an increase in a) lesson plans for the cycle I obtained an average percentage of 88.89%, increasing in cycle II to 94.45%, b) teacher activities in cycle I obtained an average percentage of 85.71%, increasing in cycle II to 96.43%, c) student activity obtained an average percentage of 84.52% then increased in cycle II to 92.86%, and d) student learning outcomes in cycle I obtained an average learning outcome of 67.46 (C). Then it increased in cycle II to 85.7 (B).